Leadership's Persuasive Communication Strategy in Reducing the Rate of Severe Discipline Violations of Soldiers (Multi-Site Study on the Pushubad Transportation Battalion and the 21st Battalion Group 2 of Kopassus) - Widarti, Eka Indri; Sinaga, Astriana Baiti (Interdisciplinary Social Studies, 2025)
In military organizations, leadership culture is typically instructive and authoritarian, with a single command center. However, leaders of Yonhub Pushubad and Yon 21 Group 2 of Kopassus may use persuasive communication strategies to reduce soldier offenses. This study aims to identify, compare, and synthesize these strategies in suppressing discipline violations at Yonhub Pushubad and Yon 21 Group 2 Kopassus. Employing a qualitative, descriptive method with a multi-site study, data were collected through in-depth interviews, participant observation, and documentation. Analysis revealed that leaders of Yonhub Pushubad applied psychodynamic, psychocultural, and meaning construction persuasive communication strategies to reduce soldier infringements. Similarly, Yon 21 Group 2 Kopassus leaders used the same three strategies to minimize transgressions. Although both units used identical strategy types, their implementation methods differed. The study concludes that leaders of Yon 21 Group 2 Kopassus are more persuasive than those of Yonhub Pushubad, as demonstrated by the greater variety and efficacy of communication strategies employed to maintain discipline. This conclusion is further supported by the lower percentage of soldier offenses in Yon 21 Group 2 Kopassus compared to Yonhub Pushubad between 2018 and 2021.